Conservation of energy and economic analysis for production of 50000MT/Annum of titanium dioxide plant by using pinch analysis - Afifah, Hapidz (2010)
Energy conservation techniques based on the Pinch Analysis is a way to minimize the energy consumption in production plant at the same time to maximize the process design. Pinch Analysis also enables the maximum interface between the utilities and process systems. Since no studies have been done on minimizing energy consumption in Titanium Dioxide Production Plant, there is a potential for energy conservation by using Pinch Analysis. The objectives of this research are to find the minimum energy requirement and to observe the effect of energy conservation to production cost and plant economics. In order to achieve the objectives, there are three main analysis are practiced which are Process Flow Diagram Analysis, Pinch Analysis and Economic Analysis. As the hot and cold stream was identified from the Process Flow Diagram, the thermal data extracted and recorded in a table. The value of ΔT min was selected between 5 to 25 °C. Next the Composite Curve and Grand Composite Curve were constructed based to the data extracted. The analysis then continued with the design of Heat Exchanger Network (HEN) where the HEN was designed at 5 different ΔT min value which are 5, 10, 15 20 and 25 °C. From HEN grid diagram analysis the minimum energy requirement can be determined and the analysis proceed with plant economic analysis that only focused to the heat exchanger and another cost that might affect after the Pinch was constructed. The results obtained from the earlier analysis are compared between the five different ΔT min to find the best. Overall analysis results in output where the best ΔT min equal to 15 °C with 50075.748 kW of energy required and a payback period of within one year of plant operation. The total cost is decreased by 35.36%